PERANAN LEMBAGA AMIL ZAKAT (LAZ) DALAM PEMBERDAYAAN MASYARAKAT MISKIN MELALUI PENGEMBANGAN USAHA MIKRO DI WILAYAH JAWA BARAT - Dulkiah, Moh. (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2017)
The purpose of this articel is to describe the role of zakat for empowering of receiver. The Implementation of zakah has social capital and civic engagemen. Social capital is a variety of entities having two characteristic in common: they all consist of some aspect of a social structure and they facilitate certain actions of individuals who are within the structure, social capital inheres in the structure of relations between person and among persons. It is lodged neither in individuals nor in physical implements of production. Civic Engagement has value derivation,namelyÂ (i) empathy, (ii) reciprocity, (iii) generosity, (iv) moral obligation, (v) social solidarity, (vi) public trust, dan (vii) public spirit. The dynamics occurred due to culture, politics of goverment and elite authoriry from any organizations.